Global patterns and environmental controls of perchlorate and nitrate co-occurrence in arid and semi-arid environments. (1st September 2015) - Jackson, W. Andrew; Böhlke, J.K.; Andraski, Brian J.; Fahlquist, Lynne; Bexfield, Laura; Eckardt, Frank D.; Gates, John B.; Davila, Alfonso F.; McKay, Christopher P.; Rao, Balaji; Sevanthi, Ritesh; Rajagopalan, Srinath; et al.
Abstract: Natural perchlorate (ClO4 − ) is of increasing interest due to its wide-spread occurrence on Earth and Mars, yet little information exists on the relative abundance of ClO4 − compared to other major anions, its stability, or long-term variations in production that may impact the observed distributions. Our objectives were to evaluate the occurrence and fate of ClO4 − in groundwater and soils/caliche in arid and semi-arid environments (southwestern United States, southern Africa, United Arab Emirates, China, Antarctica, and Chile) and the relationship of ClO4 − to the more well-studied atmospherically deposited anions NO3 − and Cl − as a means to understand the prevalent processes that affect the accumulation of these species over various time scales. ClO4 − is globally distributed in soil and groundwater in arid and semi-arid regions on Earth at concentrations ranging from 10 −1 to 10 6  μg/kg. Generally, the ClO4 − concentration in these regions increases with aridity index, but also depends on the duration of arid conditions. In many arid and semi-arid areas, NO3 − and ClO4 − co-occur at molar ratios (NO3 − /ClO4 − ) that vary between ∼10 4 and 10 5 . We hypothesize that atmospheric deposition ratios are largely preserved in hyper-arid areas that support little or no biological activity (e.g. plants or bacteria), but can be altered in areas with more active biological processes including N2 fixation, N mineralization, nitrification, denitrification, and microbial ClO4 − reduction, as indicated in part by NO3 − isotope data. In contrast, much larger ranges of Cl − /ClO4 − and Cl − /NO3 − ratios indicate Cl − varies independently from both ClO4 − and NO3 − . The general lack of correlation between Cl − and ClO4 − or NO3 − implies that Cl − is not a good indicator of co-deposition and should be used with care when interpreting oxyanion cycling in arid systems. The Atacama Desert appears to be unique compared to all other terrestrial locations having a NO3 − /ClO4 − molar ratio ∼10 3 . The relative enrichment in ClO4 − compared to Cl − or NO3 − and unique isotopic composition of Atacama ClO4 − may reflect either additional in-situ production mechanism(s) or higher relative atmospheric production rates in that specific region or in the geological past. Elevated concentrations of ClO4 − reported on the surface of Mars, and its enrichment with respect to Cl − and NO3 −, could reveal important clues regarding the climatic, hydrologic, and potentially biologic evolution of that planet. Given the highly conserved ratio of NO3 − /ClO4 − in non-biologically active areas on Earth, it may be possible to use alterations of this ratio as a biomarker on Mars and for interpreting major anion cycles and processes on both Mars and Earth, particularly with respect to the less-conserved NO3 − pool terrestrially.